Dopamine-driven mitochondrial reverse electron transport in immune cells mediates gut–brain ROS signaling during sleep deprivation - Yan Zhang; Jae-Hyuk Lee; Ziqi Yu; Yinrui Tao; Suman Rimal; Yanzi He; Lei Lv; Bingwei Lu; Yong Ping (Proceedings of the National Academy of Sciences, 2026)
Sleep deprivation (SD), together with inevitable stress inherent to conventional SD protocols, can induce oxidative stress and inflammation, thereby increasing the risk of premature death. However, the source and signaling pathways underlying reactive oxygen species (ROS) generation remain unclear. Here, we demonstrate that both mechanical and thermogenetic SD, along with possible stress induced by both protocols, lead to initial ROS accumulation in Drosophila gut subregions, including the proventriculus (PV) and PV-resident hemocytes, via upregulation of dopamine (DA) biosynthesis. Intriguingly, DA acts unconventionally by activating mitochondrial reverse electron transfer (RET), presumably through modifying interactions between the respiratory complex I proteins NDUFV1 and NDUFS3. RET-ROS elicits hemolymphatic IMD/Relish-mediated antibacterial defense. However, during chronic SD, downregulation of the Drosophila APOE/D ortholog Neural Lazarillo promotes the recruitment of hemocytes to the central brain and, together with this process, leads to widespread neuronal ROS accumulation in an Alzheimer’s disease (AD) fly model. Inhibiting RET or hemocytic DA levels extends the survival of animals under chronic SD. Our work reveals DA-driven RET-ROS in innate immune cells during SD, highlights the pivotal role of a gut-innate immune-brain crosstalk in mediating the effect of SD manipulation on aging and AD pathogenesis, and suggests ways to lessen the consequence of SD, a profound health issue in modern society.